2011
DOI: 10.1111/j.1746-1561.2011.00648.x
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Academic Achievement and Psychosocial Variables in Adolescents With Cystic Fibrosis

Abstract: Adolescents with CF require supports in school that foster their sense of self-efficacy and accommodations that address the learning time lost from extended health-related absences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 38 publications
(75 reference statements)
1
21
0
2
Order By: Relevance
“…First, CF Transmembrane Conductance Regulator (CFTR) is expressed in neurons [16] and expressed differentially during the growth of fetuses with and without CF, with unknown effects on development [17]. While children with CF typically have normal global intelligence [18], studies have demonstrated neurocognitive impairment in specific domains, including memory and executive function, in individuals with CF throughout the life span [19][20][21]. In a disease marked by increasing loss of pulmonary function, effects of hypoxia on neurocognition would be expected to worsen with progression of disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, CF Transmembrane Conductance Regulator (CFTR) is expressed in neurons [16] and expressed differentially during the growth of fetuses with and without CF, with unknown effects on development [17]. While children with CF typically have normal global intelligence [18], studies have demonstrated neurocognitive impairment in specific domains, including memory and executive function, in individuals with CF throughout the life span [19][20][21]. In a disease marked by increasing loss of pulmonary function, effects of hypoxia on neurocognition would be expected to worsen with progression of disease.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, adults with CF who grew up in an era before newborn screening may more likely have suffered failure to thrive and early malnutrition than children born in later cohorts. Finally, the complex daily treatment burden coupled with recurring absences from educational or occupational settings for medical treatment [18,22] may increase demands on organization, memory, task-efficiency, and executive function for individuals with ADHD who also have CF, which may outstrip compensatory capacities and increase functional impairment associated with ADHD [23].…”
Section: Discussionmentioning
confidence: 99%
“…Billings, Moos, Miller and Gottlieb, ; Bouaddi et al, ; Colegrove and Huntzinger, ; Everhart, ; Fowler, Johnson, Welshimer, Atkinson and Loda, ; Getch, Bhukhanwala and Neuharth‐Pritchett, ; Gorodzinsky, Hainsworth and Weisman, ; Grieve et al, ; Kirkpatrick, ; McLoone, Wakefield, Butow, Fleming and Cohn, Moonie, Sterling, Figgs, and Castro, #5462). In addition to this plethora of illnesses, research on children with medical conditions covers three additional educational mediators and moderators: country specific culture (e.g., typical social network support, socioeconomic status, psychosocial environment) and support services (e.g., school psychologists, counsellors, and hospital teachers) (Barraclough and Machek, ; Fowler, Davenport and Garg, ; Harila‐Saari et al, ; St Leger, ), age (i.e., primary school and middle/high school aged children (Getch et al, ; Grieve et al, ; Grootenhuis and Last, ; Jackson, ; McLoone et al, ; Taylor, Gibson and Franck, ), and type of school service provided (i.e., home, hospital, mainstream schooling, school re‐entry. A'Bear, ; Committee on School Health, ; L. Hopkins, Wadley, Vetere, Fong and Green, ; Kaffenberger, ; McLoone et al, ; Shaw and McCabe, ; Weiss et al, ).…”
Section: School Experience Analysis Of Students With a Medical Conditmentioning
confidence: 99%
“…Kvůli pokroku v novorozeneckém screeningu, modernizaci a efektivitě komplexní terapie, stejně jako kontrole infektů u dětských pacientů, kterým byla diagnostikována CF v uplynulém desetiletí, se očekává, že přežijí do svých 50 let (Reid et al, 2011). Jen pro ilustrování pokroku a vývoje život prodlužujících intervencí lze uvést, že střední délka života byla v roce 1940 jeden rok, zatímco v roce 2006 to bylo 37 let (Grieve et al, 2011).…”
Section: "Jinakost/odlišnost" a Cystická Ibróza Jako Chronické Onemocunclassified
“…Aktivní přístup učitele, ale také jeho lidský i profesní zájem o problematiku CF a její speci ika vede k vytváření takového školního prostředí, které umožňuje žákovi s CF prožívat v edukačním procesu úspěch, a tím také stírá jinakost/odlišnost. Zkušenost s úspěchem při překonávání překážek ovlivňuje případné zvyšování míry pocitu sebevědomí a sebeúcty žáka s CF (Grieve et al, 2011). Úprava školního prostředí je v případě edukace žáků s CF z důvodu rizik plynoucích z jejich onemocnění opravdu velmi důležitá.…”
Section: Jinakost/odlišnost Založená Speci Iky Výchovně-vzdělávacího unclassified